Correction: Proton conductivity of a hexagonal boron nitride membrane and its energy applications. Issue 4 (20th January 2021) - Yoon, Seong In; Ma, Kyung Yeol; Kim, Tae-Young; Shin, Hyeon Suk
Abstract : Correction for 'Proton conductivity of a hexagonal boron nitride membrane and its energy applications' by Seong In Yoon et al., J. Mater. Chem. A, 2020, 8, 2898–2912, DOI: ; 10.1039/C9TA12293A .